ANALISIS STRATEGI PEMASARAN PRODUK SPARE PARTS PT. UT CABANG PADANG - Beby Purnama Sari, Siska Lusia Putri (Menara Ilmu, 2016)
The purpose of this study was to identify strengths, weakness, opportunities, and threats of PT. UT for selling spare parts and to analyze marketing strategy for selling spare parts in the PT. UT. Data collection has been done from May-October 2016. The data were collected from 20 respondents who has ever bought spare parts (external respondents) and from directors and employees of the PT. UT (internal respondents). IFAS (Internal Factors Analysis Summary), EFAS (External Factors Analysis Summary) and SWOT (Strengths Weaknesses Opportunities Threats) were used to analyze the data. The result of the study showed that from IFAS Factors effect of PT. UT on internal factors (Strength and Weakness) was very strong. Meanwhile, EFAS Factors effect of PT. UT on external factors (Opportunity and Threat) was medium.S-O strategy (Strength-Opportunity) from this study was by strengthen partnerships with customers through customer seminars. W-O strategy (Weakness-Opportunity) from this study was by providing services to heavy equipment owned by the consumer and the provision of a guarantee of spare parts are sold. Then, S-T strategy (Strength-Threat) from this study was by strengthen the promotion with regular communication links. W-T (Weakness-Threat) from this study was by openning network services for heavy equipment by using the telephone. Keywords: spare parts, IFAS, EFAS, SWOT